Combined therapy with CD4+CD25highCD127− T regulatory cells and anti‐CD20 antibody in recent‐onset type 1 diabetes is superior to monotherapy: Randomized phase I/II trial. Issue 8 (9th May 2022) - Zieliński, Maciej; Żalińska, Magdalena; Iwaszkiewicz‐Grześ, Dorota; Gliwiński, Mateusz; Hennig, Matylda; Jaźwińska‐Curyłło, Anna; Kamińska, Halla; Sakowska, Justyna; Wołoszyn‐Durkiewicz, Anna; Owczuk, Radosław; Młynarski, Wojciech; Jarosz‐Chobot, Przemysława; et al.
Abstract: Aims: Monotherapy with autologous expanded CD4 + CD25 high CD127 − T regulatory cells (Tregs) or rituximab has been documented to slow disease progression in patients with recent‐onset type 1 diabetes mellitus (T1DM). Whether a combined therapy including both drugs would further benefit this patient population is unknown. Materials and Methods: We conducted a three‐arms clinical trial to explore the efficacy and safety of the combined treatment with Tregs and rituximab in paediatric patients with T1DM. The patients were allocated to three groups: Tregs only (n = 13), Tregs + rituximab (n = 12) and control (n = 11). The key primary efficacy analyses were C‐peptide levels (mixed meal tolerance test) and the proportion of patients in remission at 12 and 24 months. Results: At month 24, as compared with the control, both treatment groups remained superior in the area under the curve of C‐peptide mixed meal tolerance test, whereas in the analysis of all visits only the combined therapy improved area under the curve at 12 and 24 months. The proportion of patients in remission was significantly higher in the combined group than in the control group at 3, 6, 9 and 21 months but not at 18 and 24 months. There was no significant difference between the Tregs only group and control group. Adverse events occurred in 80% patients, mostly in the combined group and Tregs only group. No adverse events led to the withdrawal of the intervention or death. All comparisons were performed with alpha level of 5%. Conclusions: Over 2 years, combined therapy with Tregs and rituximab was consistently superior to monotherapy in delaying T1DM progression in terms of C‐peptide levels and the maintenance of remission.